2004
DOI: 10.1139/w04-056
|View full text |Cite
|
Sign up to set email alerts
|

OmpD but not OmpC is involved in adherence ofSalmonella entericaserovar Typhimurium to human cells

Abstract: Conflicting reports exist regarding the role of porins OmpC and OmpD in infections due to Salmonella enterica serovar Typhimurium. This study investigated the role of these porins in bacterial adherence to human macrophages and intestinal epithelial cells. ompC and ompD mutant strains were created by transposon mutagenesis using P22-mediated transduction of Tn10 and Tn5 insertions, respectively, into wild-type strain 14028. Fluorescein-labeled wild-type and mutant bacteria were incubated with host cells at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…Supporting this role, OmpD was shown to be involved in the adherence of S . Typhimurium to U937 monocytes and T84 intestine epithelial cells [20]. Our results showed that OmpD is not implicated in the adherence of S .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Supporting this role, OmpD was shown to be involved in the adherence of S . Typhimurium to U937 monocytes and T84 intestine epithelial cells [20]. Our results showed that OmpD is not implicated in the adherence of S .…”
Section: Discussionmentioning
confidence: 58%
“…Other studies have shown that OmpD is involved in adherence and recognition of S . Typhimurium to human macrophages and intestinal epithelial cells, during the initial stages of infection [13], [20]. Moreover, studies based on the B1b cell antibody response showed that OmpD is a key factor in the humoral response in mice [21].…”
Section: Introductionmentioning
confidence: 99%
“…This porin lack was associated with a decrease in the virulence index of K. pneumoniae strains, as reflected by the significant modification of the kinetics of the killing of the nematodes even in strains that overexpressed an efflux pump. Involvement of porins in bacterial virulence has been mentioned by some teams (12,29,31,35). However, this is the first time that a correlation between porin expression and level of virulence has been demonstrated for K. pneumoniae.…”
Section: Discussionmentioning
confidence: 90%
“…Porins expressed by the bacteria under conditions present in the host body contribute to the stability of the outer membrane (35) and also participate in the bacterial defense against the chemical immune system, e.g., defensins and antimicrobial peptides (29). Moreover, they also play a role in bacterial adhesion and invasion (12,31). In addition to the role of efflux pumps in the colonization, it is now strongly suggested that the membrane transporters are active partners of bacterial virulence in K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the fluorescent human cells were detected by FCM and the number of adhered bacterial cells was determined. Their results showed that OmpD, but not OmpC porin, is involved in the recognition of S. enterica serovar typhimurium by human macrophages and epithelial cells [95]. The same authors later reported a method for assessing the adherence of S. enterica to host cells by measuring FITC associated fluorescence of bacteria and lipophilic dye PKH-26 associated fluorescence of eukaryotic cells, therefore eliminating the inaccuracies due to bacterial cell aggregates that mimic forward scattering of eukaryotic cells [96].…”
Section: Application Of Flow Cytometrymentioning
confidence: 99%